Plane palsy: a case of transient facial weakness during an aircraft flight. (6th July 2018) - White, Rebecca; Shackleton, David
Abstract : Changes in atmospheric pressure have been reported to cause a transient lower motor neuron weakness of the facial nerve. We report the case of a passenger on an international flight who developed a unilateral facial weakness after take-off which resolved within 45 min. The effect is thought to be due to an ischaemic neuropraxia of the facial nerve caused by increased middle ear pressure compressing the facial nerve in an exposed facial canal. The condition has been commonly reported in scuba-divers but less frequently in airline passengers. Treatment is not necessary.